The DNMT1/miR-34a Axis Is Involved in the Stemness of Human Osteosarcoma Cells and Derived Stem-Like Cells - Xiao Liang; Chang Xu; Wanchun Wang; Xiang Li (Stem Cells International)
The DNA methyltransferase 1 (DNMT1)/miR-34a axis promoted carcinogenesis of various types of cancers. However, no literature reported its contribution to the stemness of osteosarcoma cancer stem-like cells (OSLCs). We sought to determine whether the DNMT1/miR-34a axis facilitates the stemness of OSLCs. We here revealed the higher DNMT1 activity and expression, lower miR-34a expression with high methylation of its promoter, and stronger stemness of OSLCs, as manifested by elevated sphere and colony formation capacities; CD133, CD44, ABCG2, Bmi1, Sox2, and Oct4 protein amounts in vitro; and carcinogenicity in a nude mouse xenograft model, when compared to the parental U2OS cells. 5-Azacytidine (Aza-dC) repressed DNMT1 activation and upregulated miR-34a expression by promoter demethylation and suppressed the stemness of OSLCs in a dose-dependent manner. DNMT1 knockdown increased miR-34a and reduced the stemness of OSLCs. Transfection with a miR-34a mimic repressed the stemness of OSLCs but did not alter DNMT1 activity and expression. Conversely, DNMT1 overexpression declined miR-34a levels, promoting the stemness of U2OS cells. Transfection with a miR-34a inhibitor enhanced the stemness of U2OS cells, without affecting the DNMT1 activity and expression. Importantly, reexpression of miR-34a could rescue the effects of DNMT1 overexpression on miR-34a inhibition as well as the stemness promotion without affecting the activity and expression of DNMT1. Our results revealed that aberrant activation of DNMT1 caused promoter methylation of miR-34a, leading to miR-34a underexpression, and the role of the DNMT1/miR-34a axis in promoting and sustaining the stemness of OSLCs.